Anestesias peridural ou subaracnoideia, com ou sem clonidina, nas hemorroidectomias - Joao Florencio de Abreu Baptista (2006)
The pain after a hemorroidectomy procedure is a reality in spite of the achievements in the analgesia field. It is the most feared event among the patients, and many steps have been taken to fight this. Objectives 1- Doubling check, in the immediate post-operatory procedure, patientssubmitted to hemorroidectomy, the analgesic efficiency and the safety not only of the epidural anesthesia performed with ropivacaine 0,75% associated or not to the clonidine, but also the arachnidananesthesia with hyperbaric bupivacaine 0,5% associated or not to the clonidine; 2- Comparing the results of anesthesia techniques. Method 80 patients were studied and submitted to hemorroidectomy,distributed randomly into four groups according to the anesthesia type: Group l (n = 19) epidural anesthesia without clonidine; Group 2 (n = 21) epidural with 150mcg of clonidine; Group 3 (n = 19) spinal without clonidine; Group 4 (n = 21) spinal with 50 mcg of clonidine.The intensity of pain was evaluated using a visual scale of analogy 8, 12 and 24 hours after surgery procedure. The use of vasoconstrictor on the trans-operatory, the consumption of analgesics 24 hours after the operation and the vital data of the patients were registered. Results The intensity of pain eight hours after surgery was smaller on the group 4 with regard to the others, and significantly smaller on the group 4 withregard to groups l and 2, 12 hours ( p = 0,022; p = 0,001) and 24 hours ( p = 0,03; p = 0,003) after the hemorroidectomy. There wasn't significant difference on the frequency of the use of vasoconstrictors on the transoperatory among the groups (p = O, 26). The frequency of analgesic usage tended to be bigger on the groups of patients in which the clonidine wasn't used (p = O, 06). The anesthesia doesn't stimulate unexpected alterations on the vital signs. Conclusion 1- The spinal and epidural anesthesia with or without clonidine were safe and effícient; 2- The frequency of the analgesic use in the postoperative one was lesser in anesthesias where if it used the clonidina; 3- The spinal xviianesthesia added with clonidine presented better analgesic efficiency comparing to the others; 4- The clonidine contributed to the reducing of pain after the hemorroidectomy procedure when associated with bupivacaine on the spinal anesthesia.